Simulation of Orbital Fractures Using Experimental and Mathematical Approaches: A Pilot Study - Eiba, Patrik; Frydrysek, Karel; Zanganeh, Behrad; Cepica, Daniel; Marsalek, Pavel; Handlos, Petr; Timkovic, Juraj; Stembirek, Jan; Cienciala, Jakub; Onderka, Arnost; Brezik, Michal; Mizera, Ondrej (Journal of functional biomaterials, 2024)
This contribution gives basic information about the mechanical behavior of the facial part of the human skull cranium, i.e., the splanchnocranium, associated with external loads and injuries caused mainly by brachial violence. The main areas suffering from such violence include the orbit, frontal, and zygomatic bones. In this paper, as a first approach, brachial violence was simulated via quasi-static compression laboratory tests, in which cadaveric skulls were subjected to a load in a testing machine, increasing till fractures occurred. The test skulls were also used for research into the dynamic behavior, in which experimental and numerical analyses were performed. A relatively high variability in forces inducing the fractures has been observed (143-1403 N). The results lay the basis for applications mainly in forensic science, surgery, and ophthalmology.
Keywords: static loading; biomechanics; forensic science; splanchnocranium; dynamic loading; experiment; fracture; orbital; modal analysis; traumatology